HETEROSIS BREEDING OF ONION - A. F. Agafonov; V. V. Logunova (Овощи России, 2018)
One of the main directions of onion crops breeding in the world is heterosis breeding. Heterosis hybrids occupy the main place in the commodity production of onions in the Netherlands, USA, Japan and other countries. In State Register for Selection Achievements Admitted for Usage (National List) of the Russian Federation, admitted to use in 2018, made 378 cultivar of onions, including 188 (49.7%) – F1 hybrids, of which 140 – foreign breeding. A common way to create heterosis hybrids F1 onions is the use of lines with cytoplasmic male sterility (CMS) as one of the parent forms. The article presents the results of multi-year research of the laboratory of breeding and seed production of onion cultures (VNIISSOK, now FSBSI FSVC) to assess and highlight the lines of CMS onions with high combinational ability, the creation of heterosis hybrids on their basis. In 2002-2005, 229 cultivar of onion were studied to identify plants with pollen sterility and maintainer. 515 plants with CMS were isolated. In the subsequent years (2006-2010) was established 1588 maternal lines (S msms) and the fathers of maintainer (N msms). To obtain F1 hybrids with the maximum level of heterosis, the combined ability of lines and pollinators was evaluated by topcross and diallel crosses. The best lines for the complex of economically useful features with high combinational ability were included in various combinations of crosses with inbred lines in order to select high-performance hybrid combinations and to create F1 hybrids. 547 combinations of crosses of sterile lines with inbred paternal lines were carried out, on the basis of which 408 F1 hybrids were created. After testing and evaluation of them in the hybrid and breeding nurseries allocated 23. According to the results of the competitive test samples were identified, which under the names of Logran F1, Zarnitsa F1 and Solnyshko F1 transferred to the state variety test.